Round Robin : The Effective Strategy to Teaching Speaking - Badriyah, Fitrotul; Ma’rifatulloh, Sayid (Lembaga Pengembangan Bahasa Universitas Hasyim Asy'ari Tebuireng Jombang, 2025)
This research aims to investigate the effectiveness of using the Round Robin strategy to improve the speaking skills of Grade VII D students at SMPN 1 Jombang in the academic year 2024/2025. The study employs a quantitative approach with a one-group pre-test and post-test pre-experimental design. The sample consisted of students from Class VII D. Data were collected through speaking tests administered before and after the implementation of the Round Robin strategy and analyzed using a paired sample t-test. The results showed an increase in the average speaking scores 72,28 from pre-test to 88,13 scores post-test. The t-test revealed a significance value of less than 0.05, indicating a statistically significant difference between students’ speaking ability before and after using the Round Robin strategy. Therefore, it can be concluded that the Round Robin strategy is effective in enhancing students’ speaking skills.